Faecal carriage of antibiotic resistant Escherichia coli in asymptomatic children and associations with primary care antibiotic prescribing: a systematic review and meta-analysis - Bryce, Ashley (BMC Infect Dis, 2016)
BACKGROUND: The faecal reservoir provides optimal conditions for the transmission of resistance genes within and between bacterial species. As key transmitters of infection within communities, children are likely important contributors to endemic community resistance. We sought to determine the prevalence of antibiotic-resistant faecal Escherichia coli from asymptomatic children aged between 0 and 17 years worldwide, and investigate the impact of routinely prescribed primary care antibiotics to that resistance. METHODS: A systematic search of Medline, Embase, Cochrane and Web of Knowledge databases from 1940 to 2015. Pooled resistance prevalence for common primary care antibiotics, stratified by study country OECD status. Random-effects meta-analysis to explore the association between antibiotic exposure and resistance. RESULTS: Thirty-four studies were included. In OECD countries, the pooled resistance prevalence to tetracycline was 37.7 % (95 % CI: 25.9–49.7 %); ampicillin 37.6 % (24.9–54.3 %); and trimethoprim 28.6 % (2.2–71.0 %). Resistance in non-OECD countries was uniformly higher: tetracycline 80.0 % (59.7–95.3 %); ampicillin 67.2 % (45.8–84.9 %); and trimethoprim 81.3 % (40.4–100 %). We found evidence of an association between primary care prescribed antibiotics and resistance lasting for up to 3 months post-prescribing (pooled OR: 1.65, 1.36–2.0). CONCLUSIONS: Resistance to many primary care prescribed antibiotics is common among faecal E. coli carried by asymptomatic children, with higher resistance rates in non-OECD countries. Despite tetracycline being contra-indicated in children, tetracycline resistance rates were high suggesting children could be important recipients and transmitters of resistant bacteria, or that use of other antibiotics is leading to tetracycline resistance via inter-bacteria resistance transmission. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-016-1697-6) contains supplementary material, which is available to authorized users.